AN ANALYSIS OF SLANG WORDS USAGE IN HIGHER EDUCATION BY USING WHATSAPP APPLICATION - Rinaldy Alidin (XXXXXXXX, 2022)
Slang words is the one term from language that unfamilliar by learner of english. Slang words often used in common for teenagers, social group in all ages which teenagers also used slang words among their peers. Slang words could created new words and new meaning which are same in form of existing words and meaning. Slang words are rarely heard which also called as taboo language. Slang words could classified into positive and negative thoughts that depends to users of slang words in communication and using. So this research study involved higher students who using slang words in their typed message on Whatsapp application. This research study focus to determine students’ knowledge about kinds of slang words and the words that include into slang words which also their reasons in using slang words on their Whatsapp application. Researcher in this  research study used qualitative method which utilized phenomenological and case study method where researcher combined interview to gathered participants’ thoughts and observation on their Whatsapp application into this research study. The results of this research study directed into the students understanding about kinds of slang words and the reasons for using slang words in their Whatsapp application which are on typed message or posted story. Hopefully, this research can be useful for higher students and next researcher which they can use this research study as they source, for reading material to enrichig knowledge. Keywords: Slang Words, Whatsapp, Higher Students